THE INFLUENCE OF WORK-LIFE BALANCE (WLB) AND WORKLOAD ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS A MODERATING VARIABLE - Aswar, Nurul Fadilah (Journal Management & Economics Review (JUMPER), 2023)
This study aims to examine the impact of Work-Life Balance (WLB) and workload on employee performance, with motivation as a moderating variable at PT. Pelabuhan Indonesia (Persero) Region 4 Makassar. The research utilized a quantitative method with a descriptive approach, collecting data through interviews, questionnaires, and observations. Data analysis was conducted using multiple linear regression with SPSS version 29. The results of the study indicate that work-life balance and workload significantly influence employee performance. A balanced work-life balance enhances employee motivation and productivity, while a workload in line with company standards positively affects performance. Work motivation acts as a mediator linking workload with performance, highlighting the importance of considering motivational aspects in human resource management. This research provides insights for companies to understand the importance of work-life balance and appropriate workload in enhancing employee performance